KEMAMPUAN MENGGUNAKAN KALIMAT EFEKTIF DALAM KARANGAN ARGUMENTASI SISWA KELAS X SMA NEGERI 1 SOSOPAN - toras barita bayo (Institut Pendidikan Tapanuli Selatan, 2019)
This study discusses the problem of effective sentences in the essay of argumentation for class X students of Sosopan 1 Public High School. The aim is to see the students 'ability to write by paying attention to the aspects of economics and the use of spelling that is perfected in students' essays. To be able to draw conclusions in this study, the authors formulated a research problem namely